Intraoperative Fluorescence‐Guided Surgery in Head and Neck Squamous Cell Carcinoma. (3rd July 2020) - Lee, Yu‐Jin; Krishnan, Giri; Nishio, Naoki; van den Berg, Nynke S.; Lu, Guolan; Martin, Brock A.; van Keulen, Stan; Colevas, Alexander D.; Kapoor, Shrey; Liu, Jonathan T.C.; Rosenthal, Eben L.
Abstract : The rate of positive margins in head and neck cancers has remained stagnant over the past three decades and is consistently associated with poor overall survival. This suggests that significant improvements must be made intraoperatively to ensure negative margins. We discuss the important role of fluorescence imaging to guide surgical oncology in head and neck cancer. This review includes a general overview of the principles of fluorescence, available fluorophores used for fluorescence imaging, and specific clinical applications of fluorescence‐guided surgery, as well as challenges and future directions in head and neck surgical oncology. Laryngoscope, 131:529–534, 2021